Heterologous expression of human cytochrome P450 2S1 in Escherichia coli and investigation of its role in metabolism of benzo[a]pyrene and ellipticine - Mrízová, Iveta; Moserová, Michaela; Milichovský, Jan; Šulc, Miroslav; Kizek, René; Kubáčková, Kateřina; Arlt, Volker M; Stiborová, Marie (Monatshefte fur chemie, 2016)
ABSTRACT: Cytochrome P450 (CYP) 2S1 is "orphan" CYP that is overexpressed in several epithelial tissues and many human tumors. The pure enzyme is required for better understanding of its biological functions. Therefore, human CYP2S1 was considered to be prepared by the gene manipulations and heterologous expression in Escherichia coli. Here, the conditions suitable for efficient expression of human CYP2S1 protein from plasmid pCW containing the human CYP2S1 gene were optimized and the enzyme purified to homogeneity. The identity of CYP2S1 as the product of heterologous expression was confirmed by dodecyl sulfate-polyacrylamide gel electrophoresis, Western blotting, and mass spectrometry. To confirm the presence of the enzymatically active CYP2S1, the CO spectrum of purified CYP2S1 was recorded. Since CYP2S1 was shown to catalyze oxidation of compounds having polycyclic aromatic structures, the prepared enzyme has been tested to metabolize the compounds having this structural character; namely, the human carcinogen benzo[a]pyrene (BaP), its 7,8-dihydrodiol derivative, and an anticancer drug ellipticine. Reaction mixtures contained besides the test compounds the CYP2S1 enzyme reconstituted with NADPH:CYP reductase (POR) in liposomes, and/or this CYP in the presence of cumene hydroperoxide or hydrogen peroxide. High performance liquid chromatography was employed for separation of BaP, BaP-7,8-dihydrodiol, and ellipticine metabolites. The results found in this study demonstrate that CYP2S1 in the presence of cumene hydroperoxide or hydrogen peroxide catalyzes oxidation of two of the test xenobiotics, a metabolite of BaP, BaP-7,8-dihydrodiol, and ellipticine. Whereas BaP-7,8,9,10-tetrahydrotetrol was formed as a product of BaP-7,8-dihydrodiol oxidation, ellipticine was oxidized to 12-hydroxyellipticine, 13-hydroxyellipticine, and the ellipticine N2-oxide.
Keywords: Enzymes; Coenzymes; High pressure liquid chromatography